Porous titanium microsphere kyphoplasty for augmentation treatment of osteoporotic vertebral fractures: Technical report and case series - Tartara, Fulvio; Armocida, Daniele; Garbossa, Diego; Meli, Francesco; Costantino, Gabriele; Cofano, Fabio; Francaviglia, Natale (Frontiers in Surgery, 2023)
Background: Vertebral augmentation procedures (VAPs) are used in cases of persistent and unresponsive pain in patients with vertebral compression fractures (VCFs). Although VAPs is considered a safe procedure providing quick pain relief and improved physical function, some postoperative complications can occur including bone cement leakage. The material used almost exclusively is polymethyl methacrylate (PMMA) that appears to lack biological activity and osteointegration capabilities. With this study, we introduce a new filling system consisting of cannulas pre-loaded with titanium microspheres, which stabilizes and consolidates the structure of the vertebral body in treating VFCs after having carried out the kyphoplasty procedure. Methods: We report a retrospective case series of 6 patients affected by osteoporotic vertebral fractures with worsening back pain, neurologic impairment and failed conservative treatment who underwent VAP at our institute using the SPHEREPLAST (MT ORTHO s.r.l., Aci Sant’Antonio (CT), Italy) system. Results: The patients had failed an average conservative trial of 3.9 weeks before they presented to us with neurodeficit. There were 2 men and 4 women with a mean age of 74.5 years. The average hospital stay was 2 days. There were no reported perioperative complications related to cement injection, such as intraoperative hypoxia, hypotension, pulmonary embolization, myocardial infarction, neurovascular or viscera injury, or death. The VAS score significantly decreased from a mean preoperative of 7.5 (range 6–19) to 3.8 (range, 3–5) immediately after surgery and 1.8 (range 1–3). Conclusion: We report the first clinical results in a series of 6 patients treated for VCF using the microsphere system analyzing clinical result and complications regarding this new device. In patients with VCF, VAP using titanium microspheres appears to be a feasible and safe procedure with a low risk of material leakage.